2008
DOI: 10.1002/jbm.a.31810
|View full text |Cite
|
Sign up to set email alerts
|

High concentration of residual aluminum oxide on titanium surface inhibits extracellular matrix mineralization

Abstract: In the present study we characterized titanium (Ti) surfaces submitted to different treatments and evaluated the response of osteoblasts derived from human alveolar bone to these surfaces. Five different surfaces were evaluated: ground (G), ground and chemical etched (G1-HF for 60 s), sand blasted (SB-Al(2)O(3) particles 65 mum), sand blasted and chemical etched (SLA1-HF for 60 s and SLA2-HF for 13 s). Surface morphology was evaluated under SEM and roughness parameters by contact scanning instrument. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
1
20
1
3
Order By: Relevance
“…The topography of Ti surfaces must be extensively analyzed using the classical amplitude and frequency parameters and also other parameters describing the surface organization (Bigerelle et al 2002). Different parameters have been recommended for 3D characterization of surface roughness (Canabarro et al 2008;Wennerberg et al 1998). The current results confirmed that Ra may not be sufficient in describing the surface morphology.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The topography of Ti surfaces must be extensively analyzed using the classical amplitude and frequency parameters and also other parameters describing the surface organization (Bigerelle et al 2002). Different parameters have been recommended for 3D characterization of surface roughness (Canabarro et al 2008;Wennerberg et al 1998). The current results confirmed that Ra may not be sufficient in describing the surface morphology.…”
Section: Discussionsupporting
confidence: 77%
“…These methods include scanning electron microscopy (SEM), confocal laser scanning microscopy, tactile microscopy, optical profilometry, scanning force microscopy, contact scanning instruments and noncontact laser profilometry (Al-Nawas et al 2001;Bigerelle et al 2002;Canabarro et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…10 In fact, TiO 2 is commonly used as a passivation layer in dental, orthopedic, and cardiovascular implants. [11][12][13] Having a conformal coating of TiO 2 over the alumina membrane is important to minimize corrosion and improve cell compatibility. Previous work by A. Canabarro et al has indicated that cells grown on TiO 2 surfaces contaminated by small amounts of alumina exhibit impaired activity; for example, contamination by alumina may lead to impaired mineralization of matrix by osteoblasts (bone cells).…”
Section: How Would You…mentioning
confidence: 99%
“…Besides the biological effects of remnants of aluminum oxide on grit-blasted surfaces (Canabarro et al, 2008), implications of this surface modification in the fatigue behavior, which is the main cause of premature failure of metallic implants, become relevant. This investigation has shown that fatigue resistance increases when blasting with zirconia particles but considerably decreases when using alumina ones.…”
Section: Discussionmentioning
confidence: 99%